Early warning indicator model of financial developments using an ordered logit - Hans-Eggert Reimers (Hochschule Wismar, Fakultät für Wirtschaftswissenschaften, 2012)
The recent financial crisis has demonstrated in an impressive way that boom/bust cycles can have devastating effects on the real economy. This paper aims at contributing to the literature on early warning indicator exercises for asset price development. Using a sample of 17 industrialised OECD countries and the euro area over the period 1969 Q1 - 2011 Q2, an asset price composite indicator incorporating developments in both stock and house price markets is constructed. The latter is then further developed in order to identify periods that can be characterised as asset price booms and busts. The subsequent empirical analysis is based on an ordered logit-type approach incorporating several monetary, financial and real variables. Following some statistical tests, credit aggregates, the interest rate spread together with the house price growth gap and stock price developments appear to be useful indicators for the prediction of asset price developments.
Keywords: E37; E44; E51; G01; 330; Börsenkurs; Immobilienpreis; Bubbles; Wirtschaftsindikator; Frühwarnsystem; Prognoseverfahren; OECD-Staaten; Eurozone